PERENCANAAN JARINGAN IRIGASI D.I LUNDAR KECAMATAN PANTI - KABUPATEN PASAMAN - Ronaldo, Ronaldo; Priana, Surya Eka; Yusman, Ana Susanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The Lundar area, Panti sub-district, Pasaman Regency, the majority of the people are farmers, but in that area there are still many plots of community rice fields where the flow is not sufficient, so there are still plots of rice fields that are not drained by water. The purpose of this research is to make it easier for farmers to manage their rice fields in order to get good yields for the farmers around them. The planning used is the planning of primary irrigation channels and secondary irrigation channels. The research method uses the haspers and gumbel calculation method. From the results of the calculation of the dimensions of the canal planning, the results of the calculation of the primary channel planning where the Q value of 7.17 m³/s is greater than the Qmax value of 5.28 m³/s and the planning of the secondary channel where the Q value is 5.57 m³/s is greater than the Qmax value of 5.28 m³/d. From the results of calculations using the gumbel method for R 5TH is 428 mm and the results of calculations using the haspers method with a Q value of 5.48 m³/s. The results of data analysis and calculations can be used as a reference for related agencies such as the Irrigation Service, or other agencies.